Is it possible to humanize medicine? Reflections regarding the use of Cinema in Medical Education - Pablo González Blasco (O Mundo da Saúde)
The central question of this paper is translated in a question: Is it possible to humanize medicine? The already long experience that the author has in the use of Cinema in Medical Education – in the national and international context – is the source of elements to answer this vital question. The answer includes a kind of factorial thinking unfolded in other questions and their answers. First of all: What is necessary to humanize? Projects of humanization that do not reach the person, the human being, and are thus restricted to public policies do not succeed. The second question is: How do we humanize with efficiency? Good will is not enough, or enthusiastic dedication, to humanize in a sustainable way. Some methodology is necessary. In the third place, a question little talked about in humanizing forums: How costly is to humanize? Until one use incredible high budgets to promote technology, leaving to volunteers without financial resources attempts of humanization, no transformation humanization seeks will be possible. Finally, the critical question: Do we really want to be humanized? Because humanizing implies reaching the heart of humans, which plays the leading role in all processes related to health, in order to transform it, to create a promise of personal order, to face professional and personal challenges. Humanizing is thus to replace oneself in life as a person, having a humanistic attitude, in order to make one’s own life a focus of effective humanization both in medicine and in life.